Spiritually-Oriented Cognitive-Behavioral Family Therapy - Turgut, Tuğba; Ekşi, Füsun (EDAM, 2020)
A great many factors influence human life. Among these are individuals’ religious and spiritual orientations, whose importance cannot be understated as they not only affect how individuals perceive and interpret themselves, events in their everyday lives, and the greater world but also shape their thoughts, feelings, and behaviors. Consequently, religious and spiritual orientations constitute an integral part of clients’ lives and are an important element that needs to be thoroughly investigated. In addition to having been integrated into individual psychological counseling approaches, religious/ spiritual orientation has become as a highly supportive element in family therapy. Spiritually-oriented applications are quite helpful when addressing problems dealt with by individuals and families. In the current study, spiritually-oriented cognitive-behavioral family therapy is addressed in light of the relevant literature. We first present a general overview of cognitive-behavioral therapy and cognitivebehavioral family therapy, after which we frame the assessment steps followed in spiritually-oriented cognitive-behavioral family therapy within a paradigm based on religion and spirituality. After that, we reveal the religious/spiritual-based cognitive-behavioral applications that may be used during family therapy. We then discuss several exercises and applications employed during spirituallyoriented cognitive-behavioral family therapy. Finally, this study seeks to fill in gaps in the relevant literature on this topic in Turkey and offer a novel perspective to practitioners and researchers.

İnsan yaşamında birçok faktör etkili olmakla birlikte dini ve manevi yönelim; bireylerin kendilerini, çevresindeki olayları ve dünyayı nasıl algıladığını ve anlamlandırdığını etkilemekte ayrıca bireylerin düşüncelerini, duygularını ve davranışlarını şekillendirmektedir. Bu doğrultuda dini ve manevi yönelimin danışanların önemli bir parçasını oluşturduğu, terapi sürecinde de üzerinde durulması gereken önemli bir bileşen olduğu düşünülmektedir. Dini ve manevi yönelim bireysel psikolojik danışma yaklaşımlarına entegre edilmekle birlikte, aile terapileri sürecinde de oldukça destekleyici bir unsur olarak karşımıza çıkmaktadır. Aile bireylerinde ve aile sisteminde yer alan problemleri ele alırken manevi yönelimli uygulamalar oldukça işlevsel görünmektedir. Bu doğrultuda bu çalışmada manevi yönelimli bilişsel davranışçı aile terapisinin ilgili literatür çerçevesinde ele alınması amaçlanmaktadır. Öncelikle BDT ve bilişsel davranışçı aile terapisine genel bir bakış sunulmakta, ardından manevi yönelimli bilişsel davranışçı aile terapisi sürecinde değerlendirme aşamaları, terapinin din ve maneviyatla çerçevelendirilmesi, aile terapisi sürecinde kullanılabilecek dini-manevi temelli bilişsel davranışçı uygulamalar açıklanmakta ve son olarak manevi temelli bilişsel davranışçı aile terapisiyle ilgili gerçekleştirilen uygulamalara yer verilmektedir. Bu çalışmanın özellikle ülkemizde eksik kalan noktaları dolduracağı, alandaki uygulayıcılara ve araştırmalara farklı bir perspektif sağlayacağı ve katkı sunacağı düşünülmektedir.
Manevi Yönelimli Bilişsel Davranışçı Aile Terapisi
Keywords: Spirituality; Family Therapy; Cognitive-Behavioral Therapy; Spiritually-Oriented Cognitive-Behavioral Family Therapy; Maneviyat; Aile Terapisi; Bilişsel Davranışçı Terapi; Manevi Yönelimli Bilişsel Davranışçı Aile Terapisi